Observer Design for the Hodgkin-Huxley Neuronal Model - Meric CETIN; Selami BEYHAN (International Journal of Applied Methods in Electronics and Computers, 2016)
Hodgkin-Huxley (HH) neuronal model has been widely accepted neuronal model in neuroscience. The variation of the ionic currents in neuron cell causes the variations in the membrane potential. The level of membrane potential indicates the activation and inactivation dynamics. In this paper, in order to observe the unmeasurable states and parameters of HH neuron accurately, Runge-Kutta discretization based nonlinear observer is designed. In numerical simulations, the membrane potential is measured and the ionic currents are estimated. The numerical results provide accurate estimation results that can be used both in monitoring and control of neuron dynamics.